Syria : a history of the last hundred years - McHugo, John, 1951- (New York : The New Press, 2015)
Charts the history of Syria from World War I to the present, documenting the nation's attempts at independence, the consequences of the Cold War and the Arab-Israeli conflicts, the rise of ISIS, and the rule of the Assad regimes.
The land that once was known as Shaam -- French rule, 1920-1946 -- From independence to Hafez al-Assad, 1946-1970 -- Hafez al-Assad, 1970-2000: foreign policy challenges -- Inside the Syria of Hafez al-Assad, 1970-2000 -- Bashar al-Assad, 2000-: from succession to civil war -- Drawing the threads together.
Includes bibliographical references (pages 273-278) and index.
Keywords: Syria -- History -- 20th century